Saturating light and not increased carbon dioxide under ocean acidification drives photosynthesis and growth in Ulva rigida (Chlorophyta). Issue 4 (25th January 2015) - Rautenberger, Ralf; Fernández, Pamela A.; Strittmatter, Martina; Heesch, Svenja; Cornwall, Christopher E.; Hurd, Catriona L.; Roleda, Michael Y.
Abstract Carbon physiology of a genetically identified Ulva rigida was investigated under different CO2(aq) and light levels. The study was designed to answer whether (1) light or exogenous inorganic carbon (Ci) pool is driving growth; and (2) elevated CO2(aq) concentration under ocean acidification (OA) will downregulate CAext‐mediated <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3x0d865p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HCO3−</alternatives> dehydration and alter the stable carbon isotope (δ13C) signatures toward more CO2 use to support higher growth rate. At pHT 9.0 where CO2(aq) is <1 μmol L−1, inhibition of the known <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3x0d8667" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HCO3−</alternatives> use mechanisms, that is, direct <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3x0d868b" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HCO3−</alternatives> uptake through the AE port and CAext‐mediated <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3x0d86bf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HCO3−</alternatives> dehydration decreased net photosynthesis (NPS) by only 56–83%, leaving the carbon uptake mechanism for the remaining 17–44% of the NPS unaccounted. An in silico search for carbon‐concentrating mechanism elements in expressed sequence tag libraries of Ulva found putative light‐dependent <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3x0d86c0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HCO3−</alternatives> transporters to which the remaining NPS can be attributed. The shift in δ13C signatures from –22‰ toward –10‰ under saturating light but not under elevated CO2(aq) suggest preference and substantial <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3x0d86dj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HCO3−</alternatives> use to support photosynthesis and growth. U. rigida is Ci saturated, and growth was primarily controlled by light. Therefore, increased levels of CO2(aq) predicted for the future will not, in isolation, stimulate Ulva blooms.